2019
DOI: 10.1016/j.heliyon.2019.e02648
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phospholipid vesicles containing lauric acid: physicochemical basis for process and product development

Abstract: Lauric acid (LAH) strongly inhibits the growth of acne-causing bacteria. LAH is essentially water-insoluble and the solubility of laurate (LA) salts are medium and temperature dependent. Hence, LAH/LA preparations are difficult to formulate. Here we fully characterized phospholipid vesicles containing up to 50 mol% LAH. Vesicles of dipalmitoylphosphatidylcholine (DPPC) containing LAH, at pHs 7.4 and 5.0, were characterized measuring size, charge, bilayer phase transition temperature (Tm) and permeability of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…It is also interesting to note that, in the case of Survanta at high temperatures, the Cailléparameter reaches higher values than Curosurf, and this may be associated with the fact that its composition contains a large amount of free fatty acids (FFA), from the supplementation process, as seen in lipidomic analysis, which may increase the membrane flexibility. 70 The obtained N values for Curosurf (Figure 7B) on heating in regions I and II are between 1 and 3. On cooling, we observe significant changes for one of the lamellar phases (blue △), in region I, compared to heating, since N is higher (between 4 and 6).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…It is also interesting to note that, in the case of Survanta at high temperatures, the Cailléparameter reaches higher values than Curosurf, and this may be associated with the fact that its composition contains a large amount of free fatty acids (FFA), from the supplementation process, as seen in lipidomic analysis, which may increase the membrane flexibility. 70 The obtained N values for Curosurf (Figure 7B) on heating in regions I and II are between 1 and 3. On cooling, we observe significant changes for one of the lamellar phases (blue △), in region I, compared to heating, since N is higher (between 4 and 6).…”
Section: ■ Results and Discussionmentioning
confidence: 90%
“…1) were synthesized in the form of conjugates with lauric acid with proven ability to associate with and be inserted into lipid bilayers. 26,27 Even shorter hexanoyl and decanoyl groups were shown to anchor in PC based liposomal membrane, allowing oligopeptide molecules to be presented at the outer liposome surface. 50 We compared two methods for liposome modification with the amphiphilic peptides based on the preparation of lipidpeptide films (method I) and post-insertion of the peptides into liposomal membrane (method II).…”
Section: Discussionmentioning
confidence: 99%
“…1) synthesized by Fmoc SPPS method consisted of RGD and GHK bioactive motifs, diglycyl spacer and lauric acid (C 12 ) residue. C 12 was selected to impart membranotropic properties 26,27 while ensuring better aqueous solubility compared with higher fatty acid homologues. Glycine-based spacer was previously introduced to self-assembling bioactive peptide amphiphiles owing to its low intermolecular H-bonding and β-sheet propensity.…”
Section: Synthesis and Characterization Of Peptidesmentioning
confidence: 99%
“…Another important fatty acid in the sebum composition is lauric acid (LA) 23 . LA is a saturated fatty acid with high antimicrobial activity 23 against C. acnes, Staphylococcus aureus , and Staphylococcus epidermis 26 . Furthermore, it has been revealed that LA and hBD‐2 may have a synergistic effect against C. acnes 5 …”
Section: Sebaceous Glandsmentioning
confidence: 99%